Improving school ethos may reduce substance misuse and teenage pregnancy. Issue 7594 (22nd March 2007) - Bonell, C; Fletcher, A; McCambridge, J
Abstract : Current strategies to improve teenage health are not having the desired effect. C Bonell, A Fletcher, and J McCambridge examine the evidence for a wider focus